2019
DOI: 10.1002/mgg3.824
|View full text |Cite
|
Sign up to set email alerts
|

The roles of transmembrane 6 superfamily member 2 rs58542926 polymorphism in chronic liver disease: A meta‐analysis of 24,147 subjects

Abstract: Background Some genetic association studies tried to investigate potential associations of transmembrane 6 superfamily member 2 (TM6SF2) polymorphisms with chronic liver disease. However, the results of these studies were not consistent. Thus, we performed the present meta‐analysis to explore associations between TM6SF2 polymorphisms and chronic liver disease in a larger pooled population. Methods Systematic literature research of PubMed, Web of Science, Embase, and CNKI was performed to identify eligible stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
3
15
0
1
Order By: Relevance
“…The rs10490626 polymorphism correlates with total cholesterol and LDL-C levels according to a genome-wide association study and meta-analysis [120]. The rs58542926 polymorphic variant of the TM6SF2 gene is used to identify individuals with a higher susceptibility to chronic liver diseases, especially hepatocellular carcinoma, cirrhosis, alcoholic liver disease, and nonalcoholic fatty liver disease [121,122]. LIMA1 encodes a negative regulator of cholesterol absorption, and its mutations lead to a decrease in the LIMA1 protein level [123].…”
Section: Discussionmentioning
confidence: 99%
“…The rs10490626 polymorphism correlates with total cholesterol and LDL-C levels according to a genome-wide association study and meta-analysis [120]. The rs58542926 polymorphic variant of the TM6SF2 gene is used to identify individuals with a higher susceptibility to chronic liver diseases, especially hepatocellular carcinoma, cirrhosis, alcoholic liver disease, and nonalcoholic fatty liver disease [121,122]. LIMA1 encodes a negative regulator of cholesterol absorption, and its mutations lead to a decrease in the LIMA1 protein level [123].…”
Section: Discussionmentioning
confidence: 99%
“…Though the specific role of Tm6sf2 gene is not yet known, these data point towards its contribution to NAFLD development, and hence, its translational applicability. Remarkably, a recent meta-analysis showed that rs58542926 polymorphism significantly associated with chronic liver disease in the overall population [73]. These novel data pointed towards the diagnostic ability of TM6SF2-polymorphism to identify individuals at higher risk for developing NAFLD, cirrhosis, and HCC, as well as alcohol-dependent liver disease [73].…”
Section: Genetic Murine Modelsmentioning
confidence: 98%
“…Similarly, hepatic knockdown of transmembrane 6 superfamily member 2 (Tm6sf2), a gene responsible for regulating hepatic lipid metabolism and associated with increased susceptibility to human NAFLD [73], resulted in increased hepatic fat content and decreased VLDL secretion [74]. Though the specific role of Tm6sf2 gene is not yet known, these data point towards its contribution to NAFLD development, and hence, its translational applicability.…”
Section: Genetic Murine Modelsmentioning
confidence: 99%
“…For instance, Sookoian et al [88], did not find any associations between the TM6SF2 mutation and circulating transaminases, necroinflammation and fibrosis possibly due to the low frequency of the rs58542926 polymorphism and lack of statistical power. Conversely, a meta-analysis of 24, 147 individuals affected by heterogeneous chronic liver disorders associated the TM6SF2 rs58542926 genotype with higher susceptibility to develop MAFLD, ALD, cirrhosis, and HCC than viral hepatitis [93]. In alcohol abusers affected by alcohol-related cirrhosis, the presence of the rs58542926 C > T variant represented an additional risk factor to develop HCC [94].…”
Section: Tm6sf2 Loss-of-function In Mafld: a Riddle Still To Be Unravmentioning
confidence: 99%